2001
DOI: 10.1002/jmri.1196
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive vessel tracking: Automated computation of vessel trajectories for improved efficiency in 2D coronary MR angiography

Abstract: A new method was investigated for improving the efficiency of ECG-gated coronary magnetic resonance angiography (CMRA) by accurate, automated tracking of the vessel motion over the cardiac cycle. Vessel tracking was implemented on a spiral gradient-echo pulse sequence with sub-millimeter in-plane spatial resolution as well as high image signal to noise ratio. Breath hold 2D CMRA was performed in 18 healthy adult subjects (mean age 46 ؎ 14 years). Imaging efficiency, defined as the percentage of the slices wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Individual patient variability affects the shape and duration of these features. Displacement of the proximal RCA in 12 subjects as a function of the cardiac phase [14]. These measurements were made from 2-D breath held magnetic resonance images, and correlate well with results obtained in this study as shown in Fig.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Individual patient variability affects the shape and duration of these features. Displacement of the proximal RCA in 12 subjects as a function of the cardiac phase [14]. These measurements were made from 2-D breath held magnetic resonance images, and correlate well with results obtained in this study as shown in Fig.…”
Section: Discussionsupporting
confidence: 85%
“…A plot of RCA displacement as a function of the cardiac cycle found in [14] (see Fig. 5) is very similar to Fig.…”
Section: A Comparison With Previous Studies: Cardiac Motionsupporting
confidence: 67%
“…No statistical difference (P = .06) was found between the body mass index of subjects with CAD risk factors (mean, 25 6 5; range, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and healthy subjects (mean, 22 6 4; range, [20][21][22][23][24][25][26][27][28][29][30]. Subjects with CAD risk factors were significantly older than healthy subjects (P , .001), while there was no significant difference in age between men and women with CAD risk factors (P = .7).…”
Section: Resultsmentioning
confidence: 92%
“…Previously proposed solutions-including vessel tracking (15)(16)(17)(18)(19), subject-specific acquisition windows (20), and adaptive trigger delays (21-23)-cannot guarantee preservation of the orthogonality required for optimal two-dimensional wall imaging and accurate quantitative assessment. Another challenge facing successful vessel wall imaging is the inherent requirement of blood signal nulling.…”
Section: Cardiac Imaging: Coronary Vessel Wall 30-t Mr Imagingmentioning
confidence: 99%
“…In contrast, values listed in Table 4 refer to actual coronary displacement. On the other hand, recent studies using slice-following techniques demonstrated significantly improved navigator-echo efficiencies (տ70%) (28). Further study is therefore required to elucidate the exact nature of the data selected by the two approaches.…”
Section: Navigator Echoesmentioning
confidence: 99%